Movilidad urbana y transporte público. Estado sobre el orden de interacción en la ciudad - Evans Morales, Franco (2023)
Urban mobility has become an important linking element for the city and its metropolitan spaces. The text has three objectives: the first of them takes as a theoretical basis the contributions of Gutiérrez (2010; 2012) to discuss urban mobility as a social travel practice, which combines needs and capacities to satisfy it and go further of an ontological vision that prioritizes arrival at places; the second objective seeks to reflect on the task of mobility in the urban structure of the city; and the third objective takes urban mobility as a theoretical approach to analyze its implication in unequal gender relations. The methodology was based on readings and critical reviews of studies on urban mobility carried out in Latin America. It reflects and concludes that, unlike transportation, mobility is a broader field that prioritizes the needs of people to travel, as well as their multiple records of trips not made, ineffective and planned. Mobility as an object of study allows analyzing its implication within urban planning in the city, and as a theoretical approach it makes visible power relations, gender inequalities and diverse subjectivities